Pengembangan E-LKPD Berbasis Model Problem Based Learning Terintegrasi Etnokimia pada Materi Asam Basa - Ika, Risqa Putri; Erna, Maria; Hayati, Sri (FKIP University of Mataram, 2025)
This study aims to develop E-LKPD based on the Problem Based Learning (PBL) model integrated with ethnochemistry that is valid based on aspects of content feasibility, characteristics of ethnochemistry integrated problem based learning, linguistic aspects, presentation and graphics, and to determine user responses to E-LKPD when used in the learning process. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The trial subjects involved teachers and students of class XI of SMAN 2 Rimba Melintang and SMAN 15 Pekanbaru. Data were obtained through expert validation and user response questionnaires. The results of the study showed that the developed E-LKPD was declared valid and feasible to be used as one of the teaching materials, and the responses of teachers and students to E-LKPD in limited trials showed that E-LKPD was included in the very good category when used in the learning process.